Ecobiology Test of Mantangan Species (Merremia peltata (L.) Merr.) from the Bukit Barisan Selatan National Park, Lampung - Kurniawati, Kurniawati -; Muhadiono, Muhadiono; Hilwan, Iwan (Journal of Tropical Life Science, 2019)
Mantangan (Merremia peltata (L.) Merr.) is a woody liana. Nowadays, it has become invasive in Bukit Barisan Selatan National Park. The objectives of this research were to analyze: 1) effect of light intensity on the growth of mantangan in natural and artificial shade, 2) effect of sand addition to the soil media and trimming on the growth rate of mantangan. Forest profile was made at the field in three locations with three light intensity levels: low, moderate, and high. A completely randomized design by three factors: shade, soil media and trimming were used. Parameters measured were stem length, leaf and buds number, fresh and dry weight. Forest profile analysis showed that high light intensity forest was dominated bay mantangan. In contrast, growth of mantangan was inhibited in low light intensity (75% shade), with lower dry weight (1.50 g). Soil media and trimming did not affect significantly on growth of mantangan.